Accounting for well capacity in the economic decision making of groundwater users - Collie, Samuel, author; Suter, Jordan, advisor; Manning, Dale, committee member; Schneekloth, Joel, committee member (Colorado State University. Libraries, 2015)
Water conflicts unfolding around the world present the need for accurate economic models of groundwater use which couple traditional producer theory with hydrological science. We present a static optimization problem of individual producer rents, given groundwater as a variable input to production. In a break with previous literature, the model allows for the possibility of binding constraints on well capacity, which occur due to the finite lateral speed at which water moves underground. The theoretical model predicts that binding well yield constraints imply producers extract as much water as possible to maximize profit. Therefore, if producers are constrained, regions with more available water should consume more of it. We test this hypothesis empirically by modelling the effect of well yields on crop cover and water usage data. Our empirical results find that areas with higher than average well capacities tend to plant a more water intensive mix of crops, and use more groundwater. This straightforward result comes in contrast to previous economic models of groundwater use, which have assumed an interior solution to the irrigators’ profit maximization problem. Well capacity also affects how farmers respond to seasonal weather variation. Farms with high well capacity react sharply to seasonal precipitation, whereas low capacity farms show less adjustment. This research provides important inroads to understanding what drives irrigators’ behavior on the High Plains; a crucial step towards conserving this resource.
Keywords: hydrology; natural resources; groundwater; spatial economics; land use